Insulin Receptor Substrate-1 Expression Is Increased in Circulating Leukocytes of Patients with Acute Coronary Syndrome. (16th June 2011) - Jiménez-Navarro, Manuel F.; Bueno, Héctor; Alvarez-Sala, Luis; Rodríguez-Losada, Noela; Andrés, Vicente; González-Navarro, Herminia
Abstract : The mechanisms underlying the increased risk of cardiovascular disease associated with diabetes mellitus (DM) are not fully defined. Insulin resistance in human metabolic syndrome patients is associated with decreased expression of the insulin receptor substrate-2- (Irs2-) AKT2 axis in mononuclear leukocytes (MLs). Moreover, acute coronary syndrome (ACS) has been linked through genome-wide association studies to the 2q36-q37.3 locus, which contains the Irs1 gene. Here, we investigated the expression of insulin-signaling pathway genes in MLs from patients with DM, ACS, and ACS plus DM. Quantitative real-time PCR expression studies showed no differences in the mRNA levels of Irs2, Akt2, and Akt1 among all patients. However, Irs1 mRNA expression was significantly increased in patients with ACS—diabetics and nondiabetics—compared with diabetic patients without ACS (P < .02 andP < .005, resp.). The present study reveals for the first time an association between increased Irs1 mRNA levels in MLs of patients with ACS which is not related to DM.